Social skills and organizational climate in the Regional Management of Social Development of the Regional Government of Callao - Valdiviezo Torres, Miguel Angel; Zapatel Arriaga, Luis Roger Ruben; Saldana Millan, Jackeline Margot; Rodas Torres, Kelly (Universidad Ciencia y Tecnología, 2022)
In this article, the relationship between social skills and the organizational climate of the collaborators of the Regional Management of Social Development of the Regional Government of Callao, in Peru, was analyzed, based on the conceptions of Goleman and Palma as the highest representatives of each construct used. The research developed by 73 collaborators in the area of the social development of the aforementioned institution, was of a basic type, nonexperimental design, and correlational scope. Validating by experts and subsequently applying two questionnaires. In the case of Goleman’s social skills, and adaptation to the general model was made, while in the case of the organizational climate, the original scheme was followed, obtaining the reliability of 0,973 and 0,949. Finally, it was concluded that both variables presented mostly an inadequate level (59% and 64%), and the existence of a direct and very intense linear relationship of 0,979 between the variables in question. Keywords: Social skills, organizational climate, government.